2016
DOI: 10.1038/nmat4586
|View full text |Cite
|
Sign up to set email alerts
|

Directed migration of cancer cells guided by the graded texture of the underlying matrix

Abstract: Living cells and the extracellular matrix (ECM) can display complex interactions that define key developmental, physiological and pathological processes. Here, we report a new type of directed migration — which we term ‘topotaxis’ — by which cell movement is guided by the gradient of the nanoscale topographic features in the cells’ ECM environment. We show that the direction of topotaxis is reflective of the effective cell stiffness, and that it depends on the balance of the ECM-triggered signalling pathways P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(174 citation statements)
references
References 47 publications
6
168
0
Order By: Relevance
“…Various components of the extracellular matrix (ECM), such as laminin have also been implicated in modulation of cell migration (Friedl and Wolf, 2009, Petrie et al, 2009, Wirtz et al, 2011, Anton et al, 1999, Porcionatto, 2006). Directional cell migration can be guided by a variety of mechanical cues presented by ECM structures ranging in size from nanometers (nm) to microns (µm) (Kim et al, 2009a, Kim et al, 2012, Park et al, 2016). Therefore, a challenge is to develop an experimental platform that will model the mechano-chemical cellular milieu, yet remain simple and accessible to allow practical, high-throughput use.…”
Section: Introductionmentioning
confidence: 99%
“…Various components of the extracellular matrix (ECM), such as laminin have also been implicated in modulation of cell migration (Friedl and Wolf, 2009, Petrie et al, 2009, Wirtz et al, 2011, Anton et al, 1999, Porcionatto, 2006). Directional cell migration can be guided by a variety of mechanical cues presented by ECM structures ranging in size from nanometers (nm) to microns (µm) (Kim et al, 2009a, Kim et al, 2012, Park et al, 2016). Therefore, a challenge is to develop an experimental platform that will model the mechano-chemical cellular milieu, yet remain simple and accessible to allow practical, high-throughput use.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the asymmetric micro‐ and nanostructures also cause cell adhesion asymmetry when they are in contact with cells, causing cell‐cytoskeletal polarization and indirectly inducing the generation of different cellular behaviours . Previous surfaces designed for generating anisotropic cell migration have usually been constructed with gradient factors including gradient arrays or gradient Young's modulus substrates . The driving forces of cell migration triggered by this type of microstructure are mainly derived from the gradient effect factor of the surface.…”
Section: Figurementioning
confidence: 99%
“…[123] Recently, Levchenko and colleagues described the guided migration of invasive and non-invasive melanoma cells according to the gradient in matrix nanotopograpy. [124] They showed that invasive (non-invasive) cells migrated towards sparser (denser) areas and concluded that the topotactic response depends on both the density and structure of the ECM, and the stiffness of the cell itself.…”
Section: Spatial Patterns Of Topographymentioning
confidence: 99%